2019
DOI: 10.21037/jss.2019.05.03
|View full text |Cite
|
Sign up to set email alerts
|

Using minimally invasive techniques adds to the value equation for select patients

Abstract: Conditions of the spine are one of the most prevalent causes of global disability, and result in a considerable portion of total health expenditures. Surgical treatment of the spine has been demonstrated in multiple studies to be a cost-effective treatment option for many patients, especially with continuing improvements in surgical technique and instrumentation. Minimally invasive spine surgery (MISS), in particular, has evolved as a valuable option in treating certain patients. Numerous studies have analyzed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 38 publications
(34 reference statements)
0
9
0
Order By: Relevance
“…8 MIS techniques being utilized to treat degenerative lumbar conditions focus on minimal bony and ligamentous resection for insertion of the interbody cage. While the maintenance of these structures may be associated with reduced postoperative pain, 9,10 it likely restricts the amount of lordosis that can be generated at the operative level. 7,11 The combined impact of the surgical approach, cage position, and built-in cage lordotic angle on the amount of postoperative SL achieved remains unclear.…”
mentioning
confidence: 99%
“…8 MIS techniques being utilized to treat degenerative lumbar conditions focus on minimal bony and ligamentous resection for insertion of the interbody cage. While the maintenance of these structures may be associated with reduced postoperative pain, 9,10 it likely restricts the amount of lordosis that can be generated at the operative level. 7,11 The combined impact of the surgical approach, cage position, and built-in cage lordotic angle on the amount of postoperative SL achieved remains unclear.…”
mentioning
confidence: 99%
“…Another study found a similar result for anterior cervical discectomy and fusion—overall charges for ambulatory anterior cervical discectomy and fusion were <50% of the charges in the inpatient setting 29. While some spine procedures are steadily shifting out of the hospital setting, one of the most prevalent and costly procedures—the lumbar fusion—remains largely an inpatient event 30–34. Some studies have reported a gradual increase in the prevalence of outpatient or ambulatory lumbar fusions in recent years; however, this trend has been halting at best 16.…”
Section: Discussionmentioning
confidence: 86%
“…29 While some spine procedures are steadily shifting out of the hospital setting, one of the most prevalent and costly proceduresthe lumbar fusion-remains largely an inpatient event. [30][31][32][33][34] Some studies have reported a gradual increase in the prevalence of outpatient or ambulatory lumbar fusions in recent years; however, this trend has been halting at best. 16 One possible explanation for this is that surgeons and medical centers question the safety of outpatient lumbar fusion, fearing that the lack of inpatient observation after surgery could increase the risk of complications.…”
Section: Discussionmentioning
confidence: 99%
“…Minimally invasive techniques have been reported to decrease intraoperative blood loss and injury to the surrounding tissues, and this may be particularly beneficial in the elderly. [3][4][5][6][7][8][9] Lumbar fusion is a more invasive procedure compared to decompression alone because it frequently involves…”
mentioning
confidence: 99%